Spatiotemporal differences of land use pattern between mountainous areas and basin areas at township scale: A case study of Yuxi City - Wu, Li; Zhou, Jing; Xie, Binggeng; Yang, Sizhong; Li, Jingzhong (Frontiers in Environmental Science, 2022)
Land use change is an important carrier and entry point of human-land research. Taking 75 towns in Yuxi City, Yunnan Province as the research unit, based on the land use and socioeconomic data from 1995 to 2018, the comprehensive evaluation model of land use/land cover change and related analysis method were used to analyze the dynamic changes of land use pattern in mountainous areas and basin areas respectively, and reveal the difference of land use evolution and its influencing factors. The results indicated that: 1) The difference in the dynamic evolution of land use in the mountainous area and the basin area has obvious stage characteristics. From 1995 to 2005, the average comprehensive dynamic degree of land use in the mountainous area was 1.7861, which was significantly higher than the 1.7033 in the basin area. From 2005 to 2018, the average comprehensive dynamic degree of land use in mountainous areas was 1.1284, which was significantly lower than 1.9427 in the basin area. 2) From 1995 to 2018, the land use degree and land use comprehensive dynamic degree increased continuously in the basin area, but increased first and then decreased in the mountainous area. The change trend of the overall land use depletion in the mountainous area was consistent with that in the basin area, but that of the mountainous area was always higher than that of the basin area. 3) The difference in land use change between mountainous areas and basin areas is mainly due to the differences of internal and external causes, that is, natural factors and socio-economic factors. The radiation and aggregation function of the basin area attracts people to migrate from the mountainous area to the basin area and promotes the ecological restoration of vegetation in the mountainous area. Since the mountainous area and the basin area are geographically adjacent, the coupling and coordination of the two is the premise and foundation of the sustainable development of the region. The mutual causality of this land use change provides a reliable basis for the regulation of mountain-basin human-land coupling relationship.